An analysis of Ph.D. examiners' reports in engineering. (3rd March 2016) - Prieto, Elena; Holbrook, Allyson; Bourke, Sid
Abstract : In recent years, there have been increasing calls for an overall transformation of the nature of engineering Ph.D. programs and the way theses are assessed. There exists a need to understand the examination process to ensure the best quality outcome for candidates in engineering. The work we present in this paper uses data collected between 2003 and 2010 for a total of 1220 Australian Ph.D. theses by analysing examiner reports. Our analysis indicates that Ph.D. theses in engineering, N  = 106, differ considerably from those in other fields in areas such as gender of candidates and examiners and the examiners' geographical location. We also found that assessment areas such as significance and contribution of the thesis, publications arising from the thesis, breadth, depth and recency of the literature review and communication and editorial correctness are areas in which the proportion of text of engineering examiners' comments differs significantly from other fields.